Biological and Engineered Topological Droplet Rectifiers. Issue 14 (30th January 2019) - Li, Jing; Li, Jiaqian; Sun, Jing; Feng, Shile; Wang, Zuankai
Abstract: The power of the directional and spontaneous transport of liquid droplets is revealed through ubiquitous biological processes and numerous practical applications, where droplets are rectified to achieve preferential functions. Despite extensive progress, the fundamental understanding and the ability to exploit new strategies to rectify droplet transport remain elusive. Here, the latest progress in the fundamental understanding as well as the development of engineered droplet rectifiers that impart superior performance in a wide variety of working conditions, ranging from low temperature, ambient temperature, to high temperature, is discussed. For the first time, a phase diagram is formulated that naturally connects the droplet dynamics, including droplet formation modes, length scales, and phase states, with environmental conditions. Parallel approaches are then taken to discuss the basic physical mechanisms underlying biological droplet rectifiers, and a variety of strategies and manufacturing routes for the development of robust artificial droplet rectifiers. Finally, perspectives on how to create novel man‐made rectifiers with functionalities beyond natural counterparts are presented. Abstract : The power of the directional and spontaneous transport of liquid droplets is revealed through ubiquitous biological processes and numerous practical applications. The latest progress in the fundamental understanding as well as the development of engineered droplet rectifiers that impart superior performance under a wide variety of working conditions, ranging from low temperature, ambient temperature, to high temperature, is discussed.